EXPLORATION OF SKIPJACK FISHING GROUND THROUGH SEA SURFACE TEMPERATURE AND CATCHES COMPOSITION ANALYZES IN PALABUHANRATU BAY WATERS - Domu Simbolon; Mario Limbong (JOURNAL OF COASTAL DEVELOPMENT, 2012)
Fishing ground condition is usually affected by oceanographic parameters. One of the oceanographic parameter that had been used in forecasting the availability of pelagic species such as skipjack is sea surface temperature (SST). Skipjack fish is the main target for boat seine net fishery in Palabuhanratu Bay from June to October 2007. Information on skipjack fishing ground availability is very important in order to optimize fishing operation. The purposes of the study are: to determine the SST distribution, to analyze the catch composition of skipjack, to determine the relationship between SST and skipjack catch, and to forecast the skipjack fishing ground in Palabuhanratu Bay from August to October 2007. The research consist of two stages. The first stage was conducted in Palabuhanratu Bay waters in August-October 2007, using survey method, with ten samples of boat seine net (payang). The second stage conducted on December 2007 to collect the SST data, which downloaded from the internet. The range of SST in Palabuhanratu Bay waters ranged from 22oC - 29oC in August 2007, 21oC - 27oC in September 2007 and  20oC - 31oC in October 2007. The SST had no significant effect on catch volume of skipjack in Palabuhanratu Bay during August until October 2007, but gave  effect to the size distribution. The big skipjack distributed at the wide range of SST, but the small skipjack distributed at the narrow range of SST. The potential fishing ground of skipjack in Palabuhanratu Bay during September 2007 was found at Teluk Ciletuh, Ujung Karangbentang, Cimaja, Teluk Cikepuh, Ujung Genteng, and Gedogan waters.